Effectiveness and safety of tumor site marking with near-infrared fluorescent clips in colorectal laparoscopic surgery: A case series study. (August 2020) - Narihiro, Satoshi; Yoshida, Masashi; Ohdaira, Hironori; Sato, Takayuki; Suto, Daisuke; Hoshimoto, Sojun; Suzuki, Norihiko; Marukuchi, Rui; Kamada, Teppei; Takeuchi, Hideyuki; Suzuki, Yutaka
Abstract: Background: In colorectal laparoscopic surgery, accuracy of tumor marking has been an important but not fully resolved issue. The tattoo marking technique or intraoperative endoscopy have been used but they either carry the risk of accidental intestinal puncture or require either longer operation times, a skilled endoscopist and/or intraoperative colon insufflation. We supposed that tumor site marking with the near-infrared fluorescent clips, ZEOCLIP FS clips (Zeon Medical Co., Ltd., Tokyo, Japan) might overcome disadvantages of both tattoo marking and intraoperative endoscopy-based tumor localization methods. This is the first report on the case series using near-infrared fluorescent marking clip. We summarize the early results in 30 patients, who underwent colorectal laparoscopic surgery; we focus particularly on effectiveness and safety of the method. Materials and methods: Thirty consecutive patients, who underwent laparoscopic surgery for colorectal cancer after previous endoscopic ZEOCLIP FS placement were enrolled from May 2019 till October 2019. The primary endpoint was the rate of intraoperative clip detection and the secondary endpoints were: the rate of adverse effects, percentage of slipped clips and usefulness of plain abdominal radiography to preoperatively confirm the clip retention. Locations of fluorescent clips were identified with a full-color fluorescence laparoscope. All operations and clip placements were performed by the same senior surgeon with sufficient experience in both procedures. Results: Fluorescent clips could be detected in 94.1% of tumor lesions. Three (2.1%) clips dropped before surgery. Plain abdominal radiography was sufficient to assess clip retention in all cases. No adverse effects related to either clip placement or clip detection were observed. Conclusion: The ZEOCLIP FS could be easily detected from the serosal side of the intestinal tract when placed 1–2 days before surgery. Fluorescent clip-guided laparoscopy may be considered a safe and effective method for localization of colorectal tumor sites. The Research Registry UIN: researchregistry5400. Highlights: Effective and satisfactory tumor marking is an unresolved problem in colorectal laparoscopic surgery. Accidental intestinal puncture make tattoo marking insufficient for tumor site marking. Near-infrared fluorescent clips may provide a valuable solution.